Effective force and economy of triathletes and cyclists - Tarragô Candotti, C.; Ribeiro, J.; Paschoal Soares, D.; Reischak de Oliveira, A.; Fagundes Loss, J.; Guimaraes, A. C. S. (Sports Biomechanics, 2007)
The effective force applied on the crank, the index of pedalling effectiveness, and the economy of movement at 60, 75, 90, and 105 rev/min cadences were examined in nine cyclists and eight triathletes. Tests were performed on two days. Maximal oxygen uptake was measured and the second ventilatory threshold was estimated on day 1 using a stationary bicycle. On day 2, the four different cadences were tested at about 5% below the second ventilatory threshold. A strain gauge instrumented clip-less pedal mounted on the bicycle enabled us to measure the normal and tangential forces exerted on the pedal, while the pedal and crank angles were monitored with the aid of a video system. Based on this information, the effective force and the index of pedalling effectiveness were calculated. Cyclists produced significantly more effective force and a higher index of pedalling effectiveness at 60 and 75 rev/min and were significantly more economic at all cadences than triathletes. The significant and positive correlation between effective force and economy at all cadences suggests that improvement of the effective force would reflect on economy.